Is it correct to trust each ultrasonography report blindly? a case report on misdiagnosis, diagnosis and management of acardiac twin pregnancy - Chandak, Pooja; Toshniwal, Shobha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Multifetal gestation is often a high-risk pregnancy and especially the monochorionic twin pregnancy significantly contributes to fetal morbidity and mortality. Acardiac twinning, earlier known as chorioangiopagus parasiticus, is the most extreme manifestation of this condition. An acardiac twin is a rare complication of multifetal pregnancy, in the literature reported at an incidence of 1% of monochorionic twin pregnancies, i.e. 1 of 35,000 pregnancies. Often results from abnormal placental vascular anastomoses. This leads to twin reversal arterial perfusion with complex pathophysiology. Here authors present a case of acardiac twin pregnancy presented at 26 weeks with the ultrasonography report suggested?? Placental teratoma of size 11×11×13 cm with polyhydramnios as there was no reason to suspect something else as the picture described in the USG report with the polyhydramnios was fitting with the diagnosis of placental teratoma but as the scan was done at taluka place and the images provided were not clear authors decided to confirm the diagnosis from fetal medicine specialist as MTP was not the option for the patient as she was 28 weeks who confirmed that as a case of acardiac twin pregnancy and the case was managed accordingly.